Development of Smart Autonomous Lawn Mower SALAM - Hazami, Che Hussain; Mohd Adib, Mohd Amin; Syahrulnaim, Mohamad Nawi; Nik Mohd Zaitul Akmal, Mustapha; Saifudin, Razali (2023)
A lawn mower is a machine that uses one or more rotating blades to cut grass to achieve an even height. The cutting height is usually predetermined by the machine’s design, which may result in some variation in grass height.